Strategies to assess web resources credibility: results of a case study in primary and secondary schools from Portugal - Terra, Ana Lúcia (2015)
In this paper, three approaches for the assessment of credibility in a web environment will be presented, namely the checklists model, the cognitive authority model and the contextual model. This theoretical framework was used to conduct a study about the assessment of web resources credibility among a sample of 195 students, from elementary and secondary schools in a municipality in Oporto district (Portugal). The practices that young people and children claim to use regarding the use of criteria for web resources selection will be presented. In addition, these results will be discussed and compared with the perceptions that these respondents have demonstrated for the use of criteria to establish or assess authorship, originality, or information resources structure. These results will be also discussed and compared with the perceptions that these respondents have demonstrated for the elements that make up each of these criteria.